Comparison of Firm Value through Capital Structure Analysis in Indonesia and Malaysia - Refi Nabillah Royadi; Soliyah Wulandari; Nurhanani Romli; Mohd Yahya bin Mohd Hussin (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2022)
The optimal funding composition can be obtained using capital structure analysis. Firm value has a big influence on the investment decisions of investors, because firm value can reflect the financial stability and the level of risk faced by the company. This study aims to determine the effect of capital structure in the form of Debt Assets Ratio (DAR) and Debt Equity Ratio (DER) on the firm value, the object in this study is a company listed on the Jakarta Islamic index and a company listed on the FTSE Bursa Malaysia Hijrah Syariah Index. While the firm value indicator used is Tobin's Q. The approach taken in this study uses a quantitative approach